Composite Weiner Hopf Equation with Variational Inequality and Equilibrium Problem - Rathee, Savita; Swami, Monika (Communications in Mathematics and Applications, 2021)
In this paper, we introduce an iteration based on compositeWeiner-Hopf equation technique to find the common solution of the set of solution of composite generalized variational inequality, set of equilibrium problem and set of fixed point of non expansive mapping in separable real Hilbert space. As the result, the strong convergence theorem of the suggested iteration has been discussed.
Keywords: CompositeWeiner-Hopf equation technique; Convergence analysis; Composite Variational inequality; Monotone operators